Safety and Efficacy of Misoprostol for the Management of Early Pregnancy Loss: A Non-Randomized Clinical Trial - Parvin, Rabeya; Nargis, Shamim Fatema; Sarkar, Most Afroza; Nessa, Khaledun; Parvin, Runa; Khanam, Rebeka (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Management of early pregnancy loss is very crucial for the safety of women. Objective: The purpose of the present study was to see the safety and efficacy of misoprostol for the management of early pregnancy loss. Methodology: This non-randomized clinical trial was conducted in the Department of Obstetrics and Gynaecology in Shaheed Ziaur Rahman Medical College Hospital, Bogra, Bangladesh from January 2007 to December 2007 for a period of 12 months. Women with early pregnancy loss who were fulfilling the selection criteria were selected as the study population during the study period. On admission all women were received a vaginal administration of 800 μg misoprostol by digital insertion into the posterior fornix through a speculum (4 tablets of 200 μg misoprostol). The interval between administration of misoprostol and expulsion of product of conception was recorded. After 7 days (8th day) they were instructed to come to the hospital to see the completeness of expulsion of product of conception by ultrasonography. If sonography shows incomplete expulsion then surgical evacuation was done. Every woman were advised to come for follow-up on 15th day. Results: A total of 200 women with first-trimester pregnancy loss were non-randomly assigned to give treatment with misoprostol. The mean with the SD of the study population was 24.95±4.17 years. In most cases expulsion occurred within 24 hours of application of misoprostol, 142(71.0%) cases completed expulsion within 48 hours, 168(84.0%) cases within 7 days, 170(85.0%) cases out of 200 cases completed expulsion occurred. Complete evacuation after the first dose was in 142(71.0%) cases and remained incomplete was 58(29.0%) cases. After administration of the second dose (85.0%) complete evacuation occurred and 30(15.0%) cases remained complete that needed surgical evacuation. Analysis was reveled statistically significant (P<0.05). Vaginal misoprostol treatment appeared to be well tolerated. Only few percent shows mild side effects. About 190(95.0%) cases required no blood transfusion. Conclusion: In conclusion the efficacy of misoprostol for the management of early pregnancy loss gives a good results with minimum adverse events. Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):152-156